Sedentary Behavior in Elementary School Children Associated with Body Mass Index - Salmatunisa, Nazela; Wibowo, Ricky; Stephani, Mesa Rahmi (TEGAR: Journal of Teaching Physical Education in Elementary School, 2021)
Technological advances are increasingly sophisticated to make lifestyle patterns easy and sedentary, especially for elementary school-age children. Just spend their daily time like watching television, playing computer and also playing video games. So reluctant to move and result in lazy to move as well as lack of activity. And cause obesity or overweight. However, not all of them show the prevalence of obesity. Therefore, the researcher aims to determine between sedentary behavior and body mass index in elementary school children. The survey method was carried out by distributing digital questionnaires to students with a total sample of 96 people and the help of Google Forms. The instrument used was the Adolescent Sedentary Activity Questionnaire (ASAQ). Descriptive analysis of the correlation between the two variables. The results show that sedentary behavior is 96.9%, body mass index is 38.5%, and there is no relationship between sedentary behavior and body mass index in elementary school students. In the future, it is hoped that there will be further research with a better research design on sedentary behavior, body mass index, and its influence.